Integration of Juridic-Sociologic Approaches in Waste Management: The Role of Government and Community Participation in Patangpuluhan Subdistrict Yogyakarta - Sari, Elly Popika; Riana, Ana (Sahabat Akademia Group, 2025)
This study explores the roles of government institutions and community participation in waste management practices in Patangpuluhan Subdistrict, Yogyakarta. It responds to the gap between formal waste management regulations and their implementation in densely populated urban areas where infrastructure and public awareness are still limited. The research argues that sustainable waste governance cannot rely solely on legal instruments; it requires active community involvement and institutional collaboration at the grassroots level. Employing a qualitative socio-legal approach, data were collected through semi-structured interviews with local government officials, community leaders, and waste bank managers, as well as through document analysis and field observations. The study investigates how national and local waste policies are interpreted, implemented, and adapted by local actors. The findings reveal multidimensional challenges, including land constraints, low compliance with regulations, and unequal access to waste facilities. Although Law No. 18 of 2008 provides a strong legal basis, its implementation in the field is constrained by the gap between “law in books” and “law in action” and the limited institutional capacity at the local level. Waste bank initiatives in several Neighborhood Units (RWs) show high participation but remain fragmented. The study’s novelty lies in its juridical-sociological lens, highlighting the interplay between normative frameworks and lived realities, and offering critical insights into the social drivers behind legal compliance in environmental governance.